IMPROVEMENT OF THE TECHNOLOGICAL PROCESS ACCOUNTING OF SALARY AT THE INDUSTRIAL ENTERPRIS - KHOMENKO, Lyudmila; YATSENKO, Natalya; MELNYCHUK, Anastasia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article regarding the working conditions of an industrial enterprise describes approaches to rational differentiation of wages taking into account the following: qualifications of jobs and employees; quantitative results of labor; working conditions, which means difficult and special sanitary and hygienic conditions of work processes; the role of an employee (profession) in production, which determines the degree of his influence on the results of collective work on manufacturing of the main production.  It is substantiated that increasing production volumes and increasing profit on investments requires constant improvement of wage accounting in case of changes in wage payment systems and wide use of modern computing equipment. It was concluded, that for small-scale production it is advisable to display the corresponding rate of payment together with the performance of various non-repetitive works or operations in the orders. For the brigade form of work, it is advisable to provide the necessary data for calculating earnings and their distribution among the members of the brigade on the reverse page of the order, taking into account the labor participation rate of each member of the brigade, which will contribute to the efficient operation of enterprises in conditions of intense competition. Rationalization of various allowances and payments additional to official salaries, as well as bonuses and rewards, which are systematic, in case of systematic reduction of total costs was performed. The implementation of the electronic form of sick leaves and the electronic register of sick leaves in the employer's personal account causes the accounting staff to rationalize the "ready for payment" operation. The organization of the technological process of accounting for both sick leaves at the expense of the social insurance fund and additional vacations for liquidators of the consequences of the accident at the Chernobyl Nuclear Power Plant is detailed. The mechanism for regulating inter-job salaries and intra-production tariffs, taking into account the qualifications of an employee, his education, the degree of responsibility for the work performed, initiative, length of service at the given enterprise, and the results of qualification certification of workers was improved. A rational report form has been developed to avoid discrepancies, numerous errors and inaccuracies in the process of accruing and transferring of preferential pensions at the expense of the funds of enterprises and organizations which are paid and delivered by employees of the Pension Fund.
Keywords: accounting appearance; variance; wages; e-medicine; pensions